2012
DOI: 10.4317/jced.50822
|View full text |Cite
|
Sign up to set email alerts
|

Periodontally accelerated osteogenic orthodontics (PAOO) - a review

Abstract: With an increasing number of adult patients coming to the orthodontic clinic, the orthodontic professional is constantly looking for ways to accelerate tooth movement. Surgical intervention to affect the alveolar housing and tooth movement has been described in various forms for over a hundred years. However, it is the spirit of interdisciplinary collaboration in orthodontics has expanded the realm of traditional orthodontic tooth movement protocols. Periodontal accelerated osteogenic orthodontics (PAOO) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 31 publications
1
71
0
9
Order By: Relevance
“…A corticotomia para auxiliar a movimentação dentária foi primeiramente descrita por LC Bryan em 1893 (AMIT et al, 2012). No entanto, foi introduzido pela primeira vez por Kole (1959) que utilizou corticotomias inter-radiculares e osteotomias supra-apicais na tentativa de aumentar a velocidade da movimentação ortodôntica, porém as osteotomias supra-apicais ofereciam grande risco para o periodonto e a vitalidade pulpar dos dentes próximos e fez com que a técnica fosse pouco utilizada.…”
Section: Técnicas Cirúrgicasunclassified
See 2 more Smart Citations
“…A corticotomia para auxiliar a movimentação dentária foi primeiramente descrita por LC Bryan em 1893 (AMIT et al, 2012). No entanto, foi introduzido pela primeira vez por Kole (1959) que utilizou corticotomias inter-radiculares e osteotomias supra-apicais na tentativa de aumentar a velocidade da movimentação ortodôntica, porém as osteotomias supra-apicais ofereciam grande risco para o periodonto e a vitalidade pulpar dos dentes próximos e fez com que a técnica fosse pouco utilizada.…”
Section: Técnicas Cirúrgicasunclassified
“…No entanto, foi introduzido pela primeira vez por Kole (1959) que utilizou corticotomias inter-radiculares e osteotomias supra-apicais na tentativa de aumentar a velocidade da movimentação ortodôntica, porém as osteotomias supra-apicais ofereciam grande risco para o periodonto e a vitalidade pulpar dos dentes próximos e fez com que a técnica fosse pouco utilizada. Duker (1975) realizou o primeiro estudo em animais utilizando a técnica descrita por Kole e anos depois as osteotomias supra-apicais foram substituídas pelos cortes limitados à porção cortical do osso alveolar surgindo as corticotomias como técnica para auxiliar e potencializar a movimentação dentária (DUKER, 1975;GENERSON et al, 1978 Orthodontics -PAOO) (AMIT et al, 2012;WILCKO et al, 2009). A terapia envolve a combinação da cirurgia de corticotomia ao enxerto alveolar.…”
Section: Técnicas Cirúrgicasunclassified
See 1 more Smart Citation
“…But in this book the science is revealed. And it is widely acknowledged as good science (Amit et al, 2012). Despite counterpoints that never fully fathom the best protocols, ODC in many forms is here to stay.…”
Section: Alfonso Caiazzomentioning
confidence: 99%
“…With this technique, one is no longer at the mercy of the pre existing alveolar volume, and teeth can be moved 2 to 3 times further in 1/3rd to 1/4th the time required for traditional orthodontic therapy. 1 Generally, we can divide the orthodontic treatment in three stages: Since it has been observed that the Stage II i.e., the retraction stage or the stage in which the extraction spaces are closed comparatively takes longer duration of time i.e., approximately half of the total orthodontic treatment time.…”
Section: Indian Journal Of Dental Advancementsmentioning
confidence: 99%